Cryptococcus neoformans in a child with CSF rhinorrhoea: A cytopathological diagnosis. Issue 9 (22nd May 2021) - Sinha, Pallavi; Singh, Meeta; Sagar, Tanu; Meher, Ravi; Kumar, Jyoti
Abstract: Cryptococcosis is caused by Cryptococcus neoformans and is fatal in children. The fungus is known to enter respiratory tract by inhalation and localizes in lungs in immunocompetent host. Patients with immunocompromised state facilitate dissemination of disease. However, disseminated cases have been described in immunocompetent HIV‐negative individuals. CSF rhinorrhoea as a predisposing cause of cryptococcal meningitis has been rarely reported. We hereby describe C. neoformans directly spreading to the meninges in 1 year child due to CSF rhinorrhoea and the fungus was detected on fluid cytology.